The Nurses’ Experience during the Caring of Coronavirus (COVID-19) Patients: A Descriptive Qualitative Study - Indah Sri Wahyuningsih; Fitria Endah Janitra; Rebriarina Hapsari; Sarinti Sarinti; Muhammad Mahfud; Failasuf Wibisono (Jurnal Keperawatan Padjadjaran, 2020)
COVID-19 transmission in the hospital environment can be catalized by a direct contact and droplets. Nurses are at the forefront of having the longest contact with the infected patient during the treatment. This research aims to dig on the deep meaning on the nurses’ practice during treating the COVID-19’s patients. This is a qualitative research design with a descriptive explorative approach. The sampling technique used in this research was a purposive side. The Data collection were carried out on five nurses who were in charge of caring the COVID-19 patients at two Semarang city’s hospitals. The research data were in the form of conversation transcripts which were analyzed using content analysis. This qualitative research analysis brought the results in three themes: first, the challenge of being a COVID-19 nurse in the emergency room, ICU and Covid care room, second, the resilience and resilience of nurses, third, the professionalism of nurses. This study indicate that the experience of nurses caring for COVID-19 patients has many challenges, namely fatigue, discomfort, anxiety, fear of contracting and stress. Anxiety creates psychological problems for nurses, which reduces the quality of service during the pandemic. Resilience and toughness are the main foundations for nurses during the pandemic.There is a need for further research with qualitative methods to look at the factors that impact on successful nursing care in COVID-19 patients during the pandemic.